Incidence of coronary drug-eluting stent fracture: A systematic review and meta-analysis - Chen, Yang; Li, Dandan; Liao, Yanhui; Yao, Xiongda; Ruan, Yuehua; Zou, Kai; Liao, Hanhui; Ding, Jingwen; Qin, Hao; Yu, Zuozhong; Zhao, Yuanbin; Hu, Longlong; et al. (Frontiers in Cardiovascular Medicine, 2022)
Background: Reported evidence of coronary stent fracture (CSF) has increased in recent years. The purpose of this study was to determine reliable estimates of the overall incidence of CSF. Methods and results: The MEDLINE, Embase and Cochrane databases were searched until March 18, 2022. Pooled estimates were acquired using random effects models. Meta-regression and subgroup analysis were used to explore sources of heterogeneity, and publication bias was evaluated by visual assessment of funnel plots and Egger’s test. Overall, 46 articles were included in this study. Estimates of CSF incidence were 5.5% (95% confidence interval [CI]: 3.7% to 7.7%) among 39953 patients based on 36 studies, 4.8% (95% CI: 3.1% to 6.8%) among 39945 lesions based on 29 studies and 4.9% (95% CI: 2.5% to 9.4%) among 19252 stents based on 8 studies. There has been an obvious increase in the incidence of CSF over the past two decades, and it seems that the duration of stent placement after stent implantation has no impact on incidence estimation. Conclusions: The incidence of CSF was 5.5% among patients, 4.8% for lesions and 4.9% for stents and increased over the past 20 years. The duration of stent placement after stent implantation was found to have no impact on the incidence of CSF, but drug-eluting stent (DES) types and right coronary artery (RCA) lesions influenced the pooled incidence.